MINAT PENYANDANG HAMBATAN PENDENGARAN TERHADAP PENGGUNAAN ALAT BANTU DENGAR - Dilla - Rahmi (Universitas Negeri Padang, 2015)
In issue in this thesis is to explain about the research interests of hearing persons with barriers to hearing aids where the sample objective is Gerkatin Member Padang. backed by the problems with the state of socialization conditions with barriers of hearing with the outside world. The purpose of this study was to describe the barriers raised interest concerning the hearing on the use of hearing aids . The method used in this research is descriptive with quantitative approach. The sampling technique was totally sampling by distributing questionnaires to the respondents that some Members Gerkatin (Indonesian Deaf Welfare Movement), amounting to 49 people. This data collection technique using a Likert scale with alternative answers strongly agree, agree, undecided, disagree and strongly disagree, with the item number 40 in respect of interest with hearing barriers to the use of hearing aid. This data collection using a percentage formula Based on the results of this study concluded that interest in hearing the barriers raised against the use of hearing aids 56% of people with hearing barriers not understand the concept of hearing aids consisting of components and forms, 63% of people with hearing barriers are keen to have a hearing aid and also very require a hearing aid to support the daily activities where the activity requires a hearing (auditory) and 45% of people with hearing barriers are highly motivated to use hearing aids and wish to have a hearing aid that can support their daily activities Keyword : Deaf, hearing aids, Descriptive Quantitative Research,